THE VELOCITY AND PRESSURE FLUCTUATIONS INSIDE HEMISPHERICAL DIMPLE - Воскобійник, В.; Воскобійник, А. (Science-based technologies, 2011)
The results of experimental researches of formation and evolution of vortex flow are presented into a hemispher-ical dimple, located on a flat surface. It is measured cross spectra of velocity fluctuation field over streamlined surface of the dimple and the plate and wall-pressure fluctuation field on streamlined surfaces. It enabled to de-fine frequencies of rotation and break up of coherent vortex structures, frequencies of shear layer self-oscillations, low-frequency resonance of self- oscillations and transversal oscillations of vortex flow inside the cavity.